Interoceptive Abilities in Inflammatory Bowel Diseases and Irritable Bowel Syndrome - Fournier, Alicia; Mondillon, Laurie; Luminet, Olivier; Canini, Fréderic; Mathieu, Nicolas; Gauchez, Anne Sophie; Dantzer, Cécile; Bonaz, Bruno; Pellissier, Sonia (Frontiers in Psychiatry, 2020)
Alexithymia is usually described by three main dimensions: difficulty identifying feelings (DIF), difficulty describing feelings (DDF), and externally oriented thinking (EOT). The most commonly used questionnaire investigating alexithymia, the Toronto Alexithymia Scale (TAS-20), supports this 3-factor structure. One important assumption is that alexithymia severity is associated to vulnerability to somatic diseases, among them gastrointestinal disorders. However, the association between alexithymia and gastrointestinal disorders is not systematic, thus questioning the role of alexithymia as a vulnerability factor for those illnesses. A recent factor analysis suggested another 4-factor structure for the TAS-20: difficulties in awareness of feelings (DAF), difficulties in interoceptive abilities (DIA), externally oriented thinking (EOT), and poor affective sharing (PAS). We assume that DIA and DAF might be more relevant to investigate the association between alexithymia and gastrointestinal disorders. The rationale is that DIA and DAF reflect impairments in emotion regulation that could contribute to an inappropriate autonomic and HPA axis homeostasis in irritable bowel syndrome (IBS), ulcerative colitis (UC), or Crohn’s disease (CD). The aim of this study was to investigate whether DIA and DAF are associated with the presence of IBS, UC or CD, while checking for anxiety, depression, parasympathetic (vagus nerve) activity and cortisol levels. We recruited control participants (n=26), and patients in remission who were diagnosed with IBS (n=24), UC (n=18), or CD (n=21). Participants completed questionnaires to assess anxiety, depression, and alexithymia. A blood sample and an electrocardiogram were used to measure the level of cortisol and parasympathetic activity, respectively. Logistic regressions with the 4-factor structure of the TAS-20 revealed that DIA was a significant predictor of IBS (W(1)=6.27, p=.01). Conversely, DIA and DAF were not significant predictors in CD and UC patients. However, low cortisol level was a significant predictor of UC (W(1)=4.67, p=.035). Additional logistic regressions based on the original 3-factor structure of TAS-20 (DIF, DDF, and EOT) showed that only DDF was a significant predictor of CD (W(1)=6.16, p<.001). The present study suggests that DIA is an important dimension for assessing potential risk for gastrointestinal diseases, in particular for IBS.